Application of Floating Trash Barrier (Trash Barrier) Based on Paralon Pipes to Hold Waste - Gita Paramita Djausal; Faranda Karenneva Utersa; Christ Theo Imanuel; Revanja Aulia Maharani (PT. TAKAZA INNOVATIX LABS, 2026)
The river in Tanjung Senang Village, Bandar Lampung City, has a problem of household waste being dumped directly into the river body. The accumulation of garbage causes the flow of water to be disrupted and risks causing flooding during heavy rains. This activity aims to install a floating trash barrier based on a paralon pipe as an effort to prevent waste from being carried away downstream. The methods carried out include location observation, problem identification, tool design, manufacturing process using hollow iron and paralon pipes as buoys, installation in the river, and periodic monitoring and cleaning. The results of the activity showed that the tool was able to hold waste at one point so that it was easier to collect and transport. The water flow continues to run smoothly and the condition of the river looks cleaner than before. Community involvement in the installation and maintenance of the equipment also helps to maintain the sustainability of the program. The application of this trash barrier can be a simple and easy-to-apply solution to help reduce river waste in residential areas.